2019
DOI: 10.3390/md17090528
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Protein ASP-3 Purified from Arca subcrenata and Its Antitumor Mechanism

Abstract: Diverse bioactive substances derived from marine organisms have been attracting growing attention. Besides small molecules and polypeptides, numerous studies have shown that marine proteins also exhibit antitumor activities. Small anticancer proteins can be expressed in vivo by viral vectors to exert local and long-term anticancer effects. Herein, we purified and characterized a novel protein (ASP-3) with unique antitumor activity from Arca subcrenata Lischke. The ASP-3 contains 179 amino acids with a molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Some data have shown that polypeptides derived from cockles can exert anti-tumor activity by inhibiting the MAPK signaling pathway[ 55 ]. Guo et al [ 56 ] found that the ASP-3 protein isolated from Arca subcrenata inhibited HepG2 cell proliferation.…”
Section: Hccmentioning
confidence: 99%
“…Some data have shown that polypeptides derived from cockles can exert anti-tumor activity by inhibiting the MAPK signaling pathway[ 55 ]. Guo et al [ 56 ] found that the ASP-3 protein isolated from Arca subcrenata inhibited HepG2 cell proliferation.…”
Section: Hccmentioning
confidence: 99%
“…ASP-3 is a protein purified from marine Arca subcrenata and exhibits a strong inhibitory effect on the proliferation of HCC cells ( Guo et al, 2019 ). Mechanistically, ASP-3 was found to effectively reduce vascular endothelial growth factor receptor (VEGFR) 2 phosphorylation (p-VEGFR2) in tumor cells and affect the vascular endothelial growth factor (VEGF) signaling pathway.…”
Section: Ncrnas As Oncogenes or Tumor Suppressors Involved In The Ant...mentioning
confidence: 99%
“…Recently, the anti-cancer properties of A. subcrenata -derived active materials have been reported in HeLa and HT-29 cells. , Specifically, the protein ASP-3 (MW = 14774.7), isolated from A. subcrenata Lischke, exerts anti-proliferative activity in HepG2 cells, with an IC 50 of 171.18 ± 18.59 μg/mL (IC 50 = 11.59 ± 1.25 μM). Moreover, in vitro studies suggest that it may exert its anti-tumor effects by inhibiting the VEGF signaling pathway …”
Section: Othermentioning
confidence: 99%
“…JG3 (51) and JG6 (52) , two structurally novel marine-derived oligosaccharides, have been shown to possess anti-angiogenic and anti-metastatic effects , as well as anti-cancer effects against liver cancer in vivo and in vitro . Specifically, JG6 suppresses BEL-7402 cell proliferation and migration in a concentration-dependent manner by inhibiting the C-X-C motif chemokine ligand 12/C-X-C motif chemokine receptor 4 axis. Additionally, the proliferation rates of BEL-7402 cells were inhibited by 22.2%, 46.5%, and 51.0% following treatment with 10, 50, and 100 μg/mL JG6, respectively.…”
Section: Othermentioning
confidence: 99%
See 1 more Smart Citation